Social Interaction in the Virtual World: The Impact of Social Media on Interpersonal Relationships in the Digital Age - Kidman, Nicole (International Journal of Social Discussion, 2024)
The rapid evolution of digital technology, particularly social media platforms, has significantly altered the landscape of social interaction. This study explores the impact of social media on interpersonal relationships in the digital age, focusing on how virtual interactions are reshaping the ways individuals connect, communicate, and maintain relationships. Using qualitative methods, including literature review and library research, this article critically examines existing research on the dynamics of social interactions within virtual environments. It addresses both the positive and negative implications of social media, highlighting how these platforms can foster a sense of community and connection while also leading to challenges such as social isolation, superficiality in relationships, and the blurring of boundaries between online and offline lives. The study further discusses the psychological effects of social media usage, such as the impact on self-esteem and the potential for increased anxiety or depression. By providing a comprehensive analysis, this article contributes to a deeper understanding of how social media is transforming social relationships and the potential long-term consequences of these changes on individual and collective well-being in a hyper-connected world.